CuZr biaxial compression 30% engineering strain - Nöhring, Wolfram G.; Hinkle, Adam R.; Pastewka, Lars (contact.engineering, 2020)
This surface is the result of a Molecular Dynamics simulation of bi-axial compression of a CuZr (50% Cu, 50% Zr) metallic glass. The initial configuration was a CuZr cube with side length 100 nm. The glass had been produced by quenching from the
melt at a rate of 1e11 K/s under fully periodic boundary conditions.

In the compression simulation, the x- and y-directions were periodic, but the z-direction was free, hence the glass had free surfaces along z. The present surface is the free surface in positive z-direction. The surface was initially atomically flat.

The glass was deformed with a rate of 1e8 s^-1 at a temperature of 100K. The temperature was controlled using a Dissipative Particle Dynamics thermostat.
This dataset contains the surface at 30% engineering strain (side length ca. 70 nm).

The simulations have been reported in the following publication:

Hinkle, A. R.; Nöhring, W. G.; Leute, R.; Junge, T.; Pastewka, L. The Emergence of Small-Scale Self-Affine Surface Roughness from Deformation. Science Advances 2020, 6 (7), eaax0847. https://doi.org/10.1126/sciadv.aax0847.

See this publication for additional information.
Keywords: FOS: Materials engineering